Topology control of satellite networks for multi-layer and multi-domain mega-constellation - XU Xiaofan; ZHANG Yueyue; CAO Xinyue; MIAO Xin; YAN Feng; DU Ping (Tongxin xuebao, 2024)
In view of the time-varying nature of the single-satellite mission in the mega constellation, the resulting overload, the vulnerability of a single node, and the high reliability requirements of the network control plane, the topology control of satellite networks for multi-layer and multi-domain mega-constellation was studied. A multi-layer and multi-domain topology description model based on Beidou grid position code was proposed. Firstly, the concepts and definitions of layer, domain, slice and element were given to realize the unified characterization of the topological characteristics of satellite nodes and inter-satellite links, and to describe the connectivity state of satellite nodes and the network topology of the entire constellation. Secondly, a topology control architecture with the on-orbit controller as the core and the ground network control as the auxiliary, was designed to provide normal operation service guarantee. Finally, the simulation platform was used to verify and analyze the subdomain division and unified characterization of the mega-constellation. The results show that the proposed topology description model can improve the real-time and accuracy of the topology control process for mega-constellation satellite networks.